2007
DOI: 10.1111/j.1365-2958.2007.05907.x
|View full text |Cite
|
Sign up to set email alerts
|

The RovA regulons of Yersinia enterocolitica and Yersinia pestis are distinct: evidence that many RovA‐regulated genes were acquired more recently than the core genome

Abstract: Summary RovA is a transcriptional activator of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 90 publications
8
69
1
1
Order By: Relevance
“…RovA is one of the best-characterized transcriptional regulators of yersiniae. It has been proposed that RovA behaves as an anti-H-NS factor to alleviate H-NS-imposed repression (15,22). Consistent with this model, in YeO8 H-NS represses inv expression at 37°C whereas at 21°C RovA overcomes H-NS-imposed repression, hence allowing inv expression.…”
Section: Effects Of Lps Temperature-dependent Variations In Susceptibsupporting
confidence: 68%
“…RovA is one of the best-characterized transcriptional regulators of yersiniae. It has been proposed that RovA behaves as an anti-H-NS factor to alleviate H-NS-imposed repression (15,22). Consistent with this model, in YeO8 H-NS represses inv expression at 37°C whereas at 21°C RovA overcomes H-NS-imposed repression, hence allowing inv expression.…”
Section: Effects Of Lps Temperature-dependent Variations In Susceptibsupporting
confidence: 68%
“…The regulatory cross talk between the genes might therefore be a good model for studying the evolution of regulatory networks in bacteria. There is evidence that H-NS acts as a silencer of laterally acquired genes in bacteria and that in Yersinia the regulator RovA is able to relieve silencing by H-NS by competing for binding at promoter regions (2,(6)(7)(8)14). Our studies show that H-NS, but not RovA, affects the expression of hreP, at least in E. coli, in a temperature-dependent manner.…”
Section: Discussionmentioning
confidence: 60%
“…In a recent study (2), it was shown that a large proportion of RovAactivated genes are repressed by H-NS. We used RovA overproduction from the P BAD promoter as a tool to analyze the effect of RovA on gene transcription in an hreP-lacZYA reporter strain (GHY19).…”
Section: Resultsmentioning
confidence: 99%
“…Nearly all RovA (SlyA)-activated genes in Yersinia spp. are repressed by H-NS, and most RovA-bound promoters are also bound by H-NS [61]. The Y. enterocolitica inv gene encoding invasin is repressed by H-NS in conjunction with Hha (called YmoA in Y. enterocolitica) [62] and derepressed by RovA.…”
Section: Counter-silencing Of H-ns and Its Functional Consequencesmentioning
confidence: 99%